Identification and Prioritization of Causal Factors of Auditors’ Professional Ethics Immaturity - Rouzbakhsh, Najmeh; Gorganli Davaji, Jomadoordi; Khozain, Ali; Khorasani, Maryam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aims to identify and prioritize the causal factors leading to the immaturity of auditors’ professional ethics. Methodology: The research methodology combines both qualitative and quantitative approaches. For gathering components related to the immaturity of professional ethics, the qualitative method utilized was grounded theory. Semi-structured interviews were conducted with 14 experts, including faculty members engaged in the auditing profession, members of the Iranian Association of Certified Public Accountants, members of the Forensic Experts Association or judicial experts, tax specialists, and financial managers of companies with a minimum of five years of auditing experience. These experts were selected purposefully using the snowball sampling method. In the quantitative section, a self-interaction matrix was constructed to perform Interpretive Structural Modeling (ISM). This part also involved the participation of 14 experts. Findings: The research results indicate that the most fundamental factor contributing to the immaturity of auditors’ professional ethics in Iran, based on the prioritization, is the diminished emphasis on ethical philosophy and religious beliefs. Moreover, the least influential factors, though ranked at the highest level, are collective cognitive errors and weaknesses in supervisory and governance institutions. Conclusion: Overall, the findings suggest that the immaturity of auditors’ professional ethics leads to the failure to achieve organizational goals. The growth of professional ethics, as highlighted by the study’s findings, can be a guiding path in this regard.